Understanding the Successful Coordination of Team Behavior - Silvan Steiner (Frontiers Research Topics, 2017)
In many areas of human life, people perform in teams. These teams' performances depend, at least partly, on team members' abilities to coordinate their contributions effectively. This includes the making of decisions and the regulation of behavior in reference to the framework provided by the social group- and task-context. Given the high relevance of a deepened and integrated understanding about the mechanisms underlying coordinated team behavior, the aim of this research topic is to provide a platform for different theoretical and methodological approaches to researching and understanding coordinated team behavior in different task contexts. The articles published in this edition offer a multifaceted insight into current work on the topic.